Alloy packaging process

By using a specific composition of sealing glass powder and a high-temperature melting process, the alloy components are sealed and joined together, solving the problem of insufficient sealing and insulation performance of alloy shells in the prior art, achieving efficient sealing and insulation effects, and improving the reliability and durability of the device.

CN119797768APending Publication Date: 2025-04-11NINGBO DUJINHUI ENVIRONMENTAL PROTECTION CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411914335.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The prior art cannot effectively solve the sealing performance and insulation performance problems of iron-nickel (cobalt) alloy shells, especially in high temperature environments, resulting in device performance degradation and high failure rate.

Method used

Two or more alloy members are sealed and joined together through a high-temperature melting process using a sealing glass powder of a specific composition, including SiO2, ZnO, Al2O3, B2O3, Na2CO3, K2CO3, TiO2 and Li2CO3. Seal glass with high strength and good sealing performance is prepared by optimizing process parameters such as high temperature insulation and cooling speed.

Benefits of technology

It realizes effective sealing of semiconductor device alloy shells with strict sealing performance, improves insulation characteristics and airtight sealing performance, improves device reliability and durability, and especially shows better performance in high temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119797768A_ABST
    Figure CN119797768A_ABST
Patent Text Reader

Abstract

The invention relates to an alloy packaging process which is characterized in that an alloy product comprising a first alloy component and a second alloy component is fused and sealed together through sealing glass, and the sealing glass is obtained by fusing the following raw material powder through a high-temperature process, the raw material powder comprises specific glass raw material components, and a specific treatment preparation process is included. According to the alloy packaging process disclosed by the invention, the air tightness of the high-temperature semiconductor device packaging structure and the insulation characteristic of the sealing glass are remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of packaging technology for alloy components, and in particular to a technology and material for sealing and bonding two or more alloy components together through a high-temperature fusion process using sealing glass. Background Art

[0002] With the upgrading of the automation industry and the rapid development of the high-end manufacturing industry, various high-end optoelectronic devices and their application fields have also been rapidly developed and the technology has been continuously iterated. Electronic components that are in power output for a long time, especially power devices working in high-temperature environments, are extremely sensitive to the surrounding environment. Once they are corroded by moisture or leak in the closed chamber, the performance indicators such as insulation resistance, leakage current or breakdown voltage of the device will be degraded, affecting normal use. The probability of failure is even higher in harsh environments such as high temperature, high pressure or strong mechanical vibration. At present, the sealing of electronic components is mostly achieved by ordinary sealing glass seams, such as the domestic DM305 system. However, the above-mentioned existing sealing glass components cannot achieve a good sealing effect, and there is no corresponding specific fusion process adapted to the specific glass component system, resulting in poor yield of electronic devices in industrial production. At the same time, for the shells and component components of the iron-nickel (cobalt) combination that have been developed, there are no products and corresponding processes that are conducive to improving the insulation isolation performance of the sealing glass and ensuring the high-level airtight sealing performance of the device.

[0003] Existing technical research has reported on related fields. For example, Chinese patent publication CN103910490A discloses a lead-free sealing glass powder, which is committed to solving the lead-free formula and focusing on its light and thermal performance, but this type of research has not made a detailed study on the iron-nickel (cobalt) high-temperature semiconductor device sealing system, nor has it achieved the insulation properties of the sealing glass and the device sealing properties under harsh working conditions. Summary of the invention

[0004] The present invention aims to solve one or more deficiencies in the above-mentioned prior art and proposes to improve the composition, production process and sealing method of glass sealing powder for alloy system.

[0005] An embodiment of the present invention provides an alloy packaging process, wherein an alloy product including a first alloy component and a second alloy component is fused and sealed together by sealing glass, wherein:

[0006] The sealing glass is obtained by melting the following raw material powders through a high-temperature process, wherein the raw material powders include the following components in parts by weight:

[0007] 50 to 80 parts by weight of SiO2, 20 to 40 parts by weight of ZnO, 5 to 20 parts by weight of Al2O3, 5 to 20 parts by weight of B2O3, 0.5 to 2 parts by weight of Na2CO3, 1 to 2 parts by weight of K2CO3, 2 to 10 parts by weight of TiO2, 25 to 60 parts by weight of Li2CO3; and preferably, wherein the mass ratio of SiO2 to Li2CO3 is 10:(4-9).

[0008] In a further preferred embodiment, the preparation of the sealing glass comprises the following steps:

[0009] Mixing the components of the raw material powder, adding an organic solvent and grinding until the components of the raw material mixed powder are evenly mixed to obtain a raw material mixed powder material;

[0010] The raw mixed powder material is heated to 1400°C to 1450°C and kept warm for 0.5 to 1 hour; then the temperature is raised to 1500 to 1550°C and kept warm for 1 to 2 hours; then the temperature is raised to 1590 to 1620°C and kept warm for 0.5 to 1 hour; then the glass blank is obtained by cooling at a cooling rate of 400 to 600°C / second, and then a sealing glass with an average particle size of 10μm to 20μm is obtained through a pulverizing process.

[0011] In an optional technical solution, the manufacturing of the sealing glass further includes the following steps:

[0012] Dispersing and bonding step: after weighing the raw material powder in proportion, prepare a dispersant in a mass percentage ratio of 1:(15-20) between the dispersant and the sealing glass, wherein the dispersant is selected from paraffin oil and / or refined paraffin; then, fully mix and cool the two at a temperature range of 90 to 100° C. to obtain glass small particles with an average particle size of about 50 mesh to 100 mesh;

[0013] Wax removal step: remove wax from the small glass particles and then crush them to obtain the sealing glass.

[0014] In an optional solution, the process of fusing and sealing the alloy product including the first alloy component and the second alloy component by sealing glass comprises the following steps:

[0015] Alloy pretreatment step: taking the first alloy component and the second alloy component and pretreating them, preferably, the pretreatment includes one or more of the steps of cleaning, polishing and degreasing;

[0016] Inert atmosphere sintering and melting bonding step: take the prepared sealing glass, the first alloy component and the second alloy component obtained after pretreatment, arrange the sealing glass at the place to be sealed between the first alloy component and the second alloy component, then place and fix them in a graphite mold, and perform sintering and melting bonding treatment under nitrogen protection.

[0017] In an optional solution, the fusion bonding process includes the following specific processing temperature and holding time:

[0018] The temperature is uniformly increased to 500-520°C at a rate of 45-55°C / min; then, the temperature is uniformly increased to 860-865°C at a rate of 20-22°C / min; then, kept at 860-865 for 5-10min; then, the temperature is uniformly increased to 990-1000°C at a rate of 5-10°C / min; then, kept at 990-1000°C for 2-4min; then, the temperature is uniformly decreased to 450-460°C at a rate of 20-25°C / min; then, the temperature is uniformly decreased to 250-260°C at a rate of 5-7°C / min; then, the temperature is uniformly decreased to 20-30°C at a rate of 80-90°C / min.

[0019] In a further preferred embodiment, the first alloy component and the second alloy component are selected from components made of an alloy containing iron and nickel; preferably, the first alloy component and the second alloy component are selected from components made of an alloy containing iron, cobalt and nickel; further preferably, the first alloy component and the second alloy component are selected from alloy components prepared from Kovar alloy.

[0020] In an optional scheme, the first alloy component is selected from the alloy guide column of the module assembly of the laser multistage tube, and the second alloy component is selected from the alloy cover bottom of the module assembly of the laser multistage tube; and preferably, the process of sealing together by sealing glass fusion also includes sealing a third alloy component with the first alloy component and the second alloy component, and the third alloy component is selected from the metal shell of the module assembly of the laser multistage tube.

[0021] According to the process of the present invention, effective sealing of the alloy housing of the semiconductor device with strict sealing performance requirements is achieved, while improving and ensuring effective insulation properties and effects.

[0022] In the following, the technical solutions and advantages of the present invention will be explained and described in more detail in conjunction with specific implementation methods. It should be understood that the contents presented in the specification and specific implementation methods are only for the purpose of more clearly illustrating the technical solutions and advantages of the present invention, and do not limit the protection scope of the present invention. Those skilled in the art can obtain the changed technical solutions based on the disclosure of the specification for various reasonable transformations. As long as they do not deviate from the spirit of the present invention, the various changed technical solutions should be understood to be included in the protection scope of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] The accompanying drawings are used to provide a further understanding of the technical solution of the present disclosure and constitute a part of the specification. Together with the specific embodiments of the present application, they are used to explain the technical solution of the present disclosure and do not constitute a limitation on the technical solution of the present disclosure.

[0024] Figure 1 is a schematic structural diagram of a module assembly of an alloy laser multistage tube sealed according to an embodiment of the present invention;

[0025] Figure 2 This is a real photo of the alloy module assembly produced according to the actual production process of the present invention;

[0026] Figure 3 It is a schematic diagram of a cross-sectional scanning electron microscope (SEM) photograph of a sealing sample obtained according to an embodiment of the present invention and a comparative example after being longitudinally cut from an alloy-sealed base. DETAILED DESCRIPTION

[0027] The present invention is described in more detail hereinafter to facilitate understanding of the invention.

[0028] Before describing the specific implementation scheme, it should be noted that those skilled in the art can select appropriate raw materials according to the enlightenment and teaching of the present disclosure, and use relevant testing equipment to perform relevant tests and obtain corresponding results. For raw materials without specific manufacturers or pathways, those skilled in the art can select raw materials that meet corresponding requirements as reaction starting materials according to the disclosure and requirements of this specification. The reaction raw materials of the process part compounds are derived from the initial products synthesized in the preamble step of the present invention, which can also be understood according to the present disclosure.

[0029] First, the main raw materials used in the present invention and the corresponding acquisition channels or raw material origins are listed in Table 1. It should be noted that the raw materials not described in the present invention are raw material varieties that can be obtained by those skilled in the art based on common technical knowledge and existing market products.

[0030] Table 1: Sources of some raw materials used in the present invention

[0031] Chemical Name source Remark Paraffin oil Shandong Nengju Chemical Co., Ltd. CAS:8012-95-1 (Refined) Paraffin Hubei Xinghengye Technology Co., Ltd. CAS:8002-74-2

[0032] The main components of the sealing glass powder of the present invention are all purchased from commercial sources. In the application field of high-performance devices, preferably, the purity of the raw materials of each component is required to reach the chemical purity level. Those skilled in the art can prepare the raw materials according to the names of the various inorganic compounds or components disclosed in this specification, and no further description is required here.

[0033] The alloy component or alloy product involved in the present invention can typically refer to an iron-nickel alloy. Since a typical Kovar alloy also contains significant cobalt, the iron-nickel alloy involved in the present disclosure can also be referred to as an iron-cobalt-nickel alloy. The alloy can be obtained from commercial channels and the corresponding devices, housings, guide pillars, etc. can be prepared through existing alloy processing technology.

[0034] The raw material components of the sealing glass of the present invention may consist only of the raw materials without containing other components; optionally, it may also contain other small amounts (eg, less than 5%, 3%, 1% of the total mass of the raw materials) of auxiliary components.

[0035] The test methods and processes used in the embodiments of the present invention and the comparative experiments will be described together with the description of the embodiments as necessary. Those skilled in the art can understand and implement the corresponding processes and tests based on the contents disclosed in the specification.

[0036] Preparation Example

[0037] Step 1) This embodiment will first describe the manufacturing process of sealing glass (sealing microcrystalline glass) suitable for fusing iron-nickel alloy.

[0038] In particular, in this preparation example, a sealing glass powder composed of the following raw materials is used (each component is calculated in parts by weight):

[0039] In typical preparation example 1, 60 parts by weight of SiO2, 25 parts by weight of ZnO, 10 parts by weight of Al2O3, 20 parts by weight of B2O3, 1 part by weight of Na2CO3, 1 part by weight of K2CO3, 5 parts by weight of TiO2, and 45 parts by weight of Li2CO3 are used. Other optional preparation examples are as follows:

[0040] Table 2: Example of basic formula preparation of sealing glass powder

[0041] Components / Preparation Example Preparation Example 1 Preparation Example 2 Preparation Example 3 Preparation Example 4 <![CDATA[SiO2]]> 60 70 55 80 ZnO 25 25 30 35 <![CDATA[Al2O3]]> 10 15 5 15 <![CDATA[B2O3]]> 20 15 10 5 <![CDATA[Na2CO3]]> 1 0.5 1 1 <![CDATA[K2CO3]]> 1 1.5 1 2 <![CDATA[TiO2]]> 5 5 10 5 <![CDATA[Li2CO3]]> 45 50 30 35

[0042] The Li2CO3, Na2CO3 and K2CO3 in the sealing microcrystalline glass raw materials described in the embodiment of the present invention will be mostly decomposed into corresponding oxide components (such as Li2O, Na2O and K2O) during the high-temperature smelting process, which can be used as the main components of the sealed microcrystalline glass together with silicon oxide. At the same time, the carbon dioxide gas released during the decomposition process also helps to clarify and remove slag from the sealed glass. Na2O and K2O in the glass can also play a role in reducing the viscosity of the glass product, which is conducive to the natural leveling during the glass sealing process. When the mass fraction ratio of Na2CO3 and K2CO3 is 1: (1 to 1.5), and the ratio of the sum of the mass fractions of Na2CO3 and K2CO3 to the mass fraction of SiO2 is less than or equal to 1:30 and greater than or equal to 1:40, the viscosity reduction and quality preservation effect is better. Experiments have found that if the sum of the mass fractions of Na2CO3 and K2CO3 and the mass fraction of SiO2 is greater than 1:30, the viscosity of the glass is too low under high-temperature sealing and fusion conditions, resulting in poor fusion between the joint and the metal. If it is less than 1:40, the crystal grains of the microcrystalline glass body will be too large, and the flow and fusion effect with the gap will be reduced. In the experiments and inventions, it will be described in more detail that, more preferably, the ratio of the sum of the mass fractions of Na2CO3 and K2CO3 to the mass fraction of SiO2 is less than or equal to 1:35 and greater than or equal to 1:40. In addition, silicon oxide SiO2, as the main component of the sealing glass, should account for more than 30% by mass of the sum of the components of the sealing glass raw materials, and preferably, it can account for more than 40% by mass of the total raw material components.

[0043] Thus, for the embodiment of the present invention, the basic components of the sealing glass powder may include SiO250 to 80 parts by weight, ZnO 20 to 40 parts by weight, Al2O35 to 20 parts by weight, B2O35 to 20 parts by weight, Na2CO30.5 to 2 parts by weight, K2CO31 to 2 parts by weight, TiO22 to 10 parts by weight, and Li2CO325 to 60 parts by weight in powder form. Optionally, the sealing glass powder may also include 1 to 10 parts by weight of a binder. In a typical solution, no additional binder may be required.

[0044] The inventors also found that a relatively large amount of Li2CO3 is used in the sealing glass powder of the present invention. During the high-temperature phase change and melting process, on the one hand, part of the Li2O generated in the gasified Li2CO3 can make the crystallization behavior of the glass slow and uniform, making the precipitated crystals more delicate, and the distribution and particle size of the crystal particles more uniform, which helps to enhance the strength of the glass and the toughness after fusion. On the other hand, the inventors surprisingly found that the excess Li2CO3 can be used as an auxiliary nucleating agent, which may be related to the small volume and clear skeleton of the molecular framework of Li oxide itself. During the crystallization process, it makes the crystals more inclined to the precipitation of spinel phase ZnAl2O4 (the presence of spinel phase ZnAl2O4 makes the glass stronger) and inhibits the generation and growth of other similar phases (such as ZnB2O4 crystals) (the volume ratio of ZnB2O4 in the final precipitated crystal phase in the sealing glass powder of the present invention is less than 5%, preferably less than 3%). Due to the reduction in the volume of ZnB2O4, other high-strength components of B oxide (B2O3) can be present in a larger proportion in the final formed crystal phase of the microcrystalline glass powder. The inventors found that after using a high proportion of Li2CO3, as long as the appropriate sintering temperature curve is controlled, other glass crystal phase inducing agents (such as phosphorus, nitrogen, and other metal nucleating agents) are not required, and the nucleation effect is better than other nucleating agents.

[0045] In the preparation examples implemented in the present invention, the mass fractions of SiO2 and Li2CO3 should be present in equal quantities and in proportion, and the preferred mass fraction ratio of SiO2 to Li2CO3 is 10:(4-9), and preferably the mass fraction ratio of SiO2 to Li2CO3 is 10:(5-8).

[0046] After determining the raw material components of Preparation Example 1, the raw materials of the sealing microcrystalline glass in various subdivided forms are mixed, an organic solvent (anhydrous ethanol is selected) is added, and the raw materials are ground until the raw materials are uniformly mixed;

[0047] The material obtained in the above steps is heated to 1400°C to 1450°C and kept warm for 0.5 to 1 hour; then the temperature is raised to 1500 to 1550°C and kept warm for 1 to 2 hours; then the temperature is raised to 1590 to 1620°C and kept warm for 0.5 to 1 hour; then the molten glass blank is rolled by a water-cooling or air-cooling rolling process at a cooling rate of 400 to 600°C / second to obtain a strip or sheet of sealing glass, and then a sealing glass powder (microcrystalline sealing glass powder) with an average particle size of 10μm to 20μm is obtained by a crushing process.

[0048] In the process of the present invention, the raw material powder is heat-insulated in a high-temperature variable temperature section so that the crystal phases of the components of the sealing glass powder are fully formed and distributed at high temperatures, especially at a temperature greater than 1550°C, ultra-high temperature insulation (such as 1590 to 1620°C) is carried out for an appropriate time so that the Li2O skeleton induced by the crystal phase is fully wrapped by other components and then grows. The inventors found that in the cooling and rolling process, the cooling rate should be controlled to be less than 800°C / second, preferably controlled and operated at a cooling rate of 400 to 600°C / second. If the cooling temperature is too high, the desired high-strength spinel phase ZnAl2O4 of the microcrystalline glass is insufficiently formed, and at the same time, the B element will compete with Zn to form a low-strength boron zinc oxide (ZnB2O4) crystal phase.

[0049] Step 2): Dispersion and bonding step: Next, take the sealing glass powder prepared by the above process, and prepare the raw materials according to the mass percentage of dispersant to sealing glass powder of 1: (15-20). In an embodiment of the present invention, the dispersant can be a composition of paraffin oil and refined paraffin (mass ratio 1:1), and refined paraffin is paraffin that has been purified and impurities removed. In other optional schemes, other related glass material dispersants can also be used. In the temperature range of 90 to 100°C, the two are fully mixed and cooled to obtain small-particle sealing glass with an average particle size of approximately 50 to 100 mesh.

[0050] Step 3): Wax removal step: Remove the small particles of sealing glass in the above step and remove the wax in the following temperature process:

[0051] The temperature curve of the wax removal treatment is: increase the temperature to 400 to 450°C at a rate of 3-3.5°C / min, and keep it warm for 4-5 minutes; increase the temperature to 550-560°C at a rate of 4-4.5°C / min, keep it warm for 10-15 minutes, and cool it down to 40-50°C at a rate of 15-25°C / min. It can then be broken according to the application to obtain sealable sealing glass.

[0052] Next, in a typical scenario, two or more iron-nickel metal alloy assemblies (in a more typical embodiment, the metal also contains a significant amount of cobalt Co, also referred to as iron-cobalt-nickel alloy) are assembled using a sealable sealing glass according to an embodiment of the present invention.

[0053] Example 1

[0054] This example describes an embodiment of fusion sealing two (or more) iron-nickel alloy metal parts together.

[0055] In the application embodiment of the present invention, it involves a high-temperature and high-precision optical element, such as a module assembly of a laser multistage tube, the schematic diagram of which is as follows Figure 1 shown. Figure 1The laser multistage tube packaging component shown in the figure includes a metal shell 100 with a cavity, a high temperature lens module 200, an alloy cover bottom 300, and an alloy guide column 400, wherein one end of a plurality of alloy guide columns 400 extends into the alloy cover bottom 300 into the cavity. In a typical application, a sealing glass 500 (whose powder or particles are arranged in a tiny joint between the two) is required to seal where the alloy guide column 400 and the alloy cover bottom 300 are connected to each other. Therefore, in the present invention, the first alloy component can be the alloy guide column 400, and the second alloy component can be the alloy cover bottom 300. In addition, the metal shell 100 and the alloy cover bottom 300 can be welded by metal solder, or they can be fused and sealed according to the sealing glass component of the present invention.

[0056] In this embodiment, the first alloy component and the second alloy component are composed of an iron-nickel alloy (such as 4j29) (commonly known as Kovar alloy). In this embodiment, 4j29 contains about 29% by mass of Ni in addition to the main Fe element, and also contains a significant amount of cobalt (Co), such as 18% by mass. Therefore, the iron-nickel alloy Kovar alloy used in this embodiment can also be described as (Fe-29Ni-18Co, or iron-nickel-cobalt alloy).

[0057] It should be noted that the process is not limited thereto, and those skilled in the art can select a suitable iron-nickel alloy to implement the process of the present invention according to the scheme disclosed in this embodiment. The specific process steps are as follows:

[0058] Step 1) Pretreatment step, taking the first alloy component and the second alloy component for pretreatment. Typical pretreatment steps may include one or more of cleaning, polishing and degreasing steps;

[0059] Step 2) Take the sealing glass described in the above preparation example of the present application (taking Preparation Example 1 as an example), place and fix the first alloy component (alloy guide pillar 400) and the second alloy component (alloy cover bottom 300) processed in step 1) together with the sealing glass, and optionally the metal shell 100 and the placed sealing glass (including the guide pillar and the cover bottom hole and between the cover bottom and the metal shell) in a graphite mold, and perform sintering and melting bonding treatment under nitrogen protection. The specific process of the treatment is:

[0060] Raise the temperature uniformly to 500-520℃ at a rate of 45-55℃ / min → Raise the temperature uniformly to 860-865℃ at a rate of 20-22℃ / min → Keep at 860-865 for 5-10min → Raise the temperature uniformly to 990-1000℃ at a rate of 5-10℃ / min → Keep at 990-1000℃ for 2-4min → Cool down uniformly to 450-460℃ at a rate of 20-25℃ / min → Cool down uniformly to 250-260℃ at a rate of 5-7℃ / min → Cool down uniformly to 20-30℃ at a rate of 80-90℃ / min.

[0061] Thus, a sealed alloy component is obtained. In this process, the module components of the mass-produced laser multistage tube are obtained. Figure 2 As shown in the photos.

[0062] For different preparation examples 1 to 4, the above fusion process is adopted to obtain embodiments 1 to 4 corresponding to each other.

[0063] Test steps:

[0064] Corresponding performance tests will be conducted for Examples 1 to 4 obtained from different preparation examples. It will be understood by those skilled in the art that comparable and identical tests will also be conducted under the same conditions for the comparative examples described below.

[0065] First, the sealing insulation characteristics of high-power and high-temperature devices were tested according to the standards and test methods in the relevant contents of GB9622.1~9622.11. The results are shown in the table below.

[0066] Table 3: Sealing glass performance test parameters

[0067]

[0068]

[0069] In addition, the sealing tube housing of the embodiment is also monitored for air tightness, specifically, the test object is taken for air tightness detection. According to the actual working environment, after the air tightness test is carried out at room temperature and pressure, the air tightness test is further carried out after aging for one week (168h) at 90°C. Five samples are prepared in parallel for each test embodiment, and the arithmetic mean of each sample is taken to obtain the final evaluation value of the sample.

[0070] Table 4: Air tightness monitoring of sealing tube housing in the embodiment (unit: m 3 .Pa / s)

[0071]

[0072] Comparative Examples 1-3

[0073] In comparative examples 1-3, the fusion connection process is exactly the same as that in Example 1. Different from the example, the comparative examples adjust or change the raw material ratios of the corresponding sealing glasses in preparation examples 1-4.

[0074] Table 5: Sealing glass raw materials of comparative preparation examples

[0075]

[0076]

[0077] In Comparative Example 1, the inventors significantly reduced the proportion of lithium carbonate (Li2CO3) used in the sealing glass; in Comparative Example 2, compared with Preparation Example 2 corresponding to the embodiment, a small amount of phosphorus compounds were added as auxiliary crystal phase formers; and in Comparative Example 3, compared with Preparation Example 3, P2O5 and ZrO2 were added at the same time as auxiliary nucleation agents.

[0078] Comparative Example 4

[0079] In Comparative Example 4, the same glass raw material components as those in Preparation Example 1 corresponding to Example 1 are used, and the same fusion connection process as that in Example 1 is used. The difference is that in Comparative Example 4, after determining the raw material ratio of the sealing glass powder, anhydrous ethanol is added and ground until the raw materials are uniformly mixed; then the obtained material is heated to 1400°C to 1450°C and kept warm for 0.5 to 1 hour; then the temperature is raised to 1500 to 1550°C and kept warm for 3 hours, and then no longer undergoes ultra-high temperature melting (greater than 1550°C), but directly rolls the molten glass blank at a cooling rate of 400 to 600°C / second through a water-cooled or air-cooled rolling process to obtain a strip or sheet of sealing glass, and then a pulverizing process is used to obtain the sealing glass powder of Comparative Example 4 with an average particle size of 10μm to 20μm. The sealing glass powder is then subjected to the same dispersion bonding and wax removal processes as those in Preparation Example 1, and the same fusion sealing process as that in Example 1 is performed.

[0080] Comparative Example 5

[0081] In Comparative Example 5, the same glass raw material components as those in Preparation Example 1 corresponding to Example 1 are used, and the same fusion connection process as that in Example 1 is used. The difference is that in Comparative Example 4, after determining the raw material ratio of the sealing glass powder, anhydrous ethanol is added and ground until the raw materials are evenly mixed; then the obtained material is heated to 1400°C to 1450°C and kept warm for 0.5 to 1 hour; then the temperature is raised to 1500 to 1550°C and kept warm for 1 to 2 hours, and then the temperature is raised to 1590 to 1620°C and kept warm for 0.5 to 1 hour; then the molten glass blank is rolled at a cooling rate of 800-1000°C / second through a water cooling process to obtain a strip or sheet of sealing glass, and then a sealing glass powder with an average particle size of 10μm to 20μm is obtained through a crushing process, and then the sealing glass powder with an average particle size of 10μm to 20μm of Comparative Example 5 is obtained through a crushing process. The sealing glass powder is then subjected to the same dispersion bonding and wax removal processes as in Preparation Example 1, and the same fusion sealing process as in Example 1.

[0082] Comparative Example 6

[0083] In this comparative example, the sealing glass components and processes are exactly the same as those in Preparation Example 1. The difference is that compared with the sintering and melting bonding process under nitrogen protection in Example 1, the specific process of the process described in this experiment is:

[0084] Raise the temperature to 500-520℃ at a rate of 45-55℃ / min → Raise the temperature to 860-865℃ at a rate of 20-22℃ / min → Keep at 860-865 for 20-25min → Cool down to 450-460℃ at a rate of 20-25℃ / min → Cool down to 250-260℃ at a rate of 5-7℃ / min → Cool down to 20-30℃ at a rate of 80-90℃ / min.

[0085] The sealed and fused components obtained in each comparative experiment were subjected to corresponding tests, and the results are shown in the table below.

[0086] Table 5: Sealing glass performance test parameters

[0087]

[0088]

[0089] Table 6: Comparative Example Sealing Tube Shell Air Tightness Monitoring (Unit: m 3 .Pa / s)

[0090]

[0091] It can be seen from the test results of the embodiments and the comparative examples that embodiments 1 and 2 have achieved relatively better results. For the comparative example, when the Li2CO3 component in the sealing glass powder raw material changes, the thermal expansion coefficient of the sealing glass itself deteriorates to a certain extent. Although the inventor believes that it should not be subject to any theoretical explanation, it is analyzed that this is related to the nucleation of the oxide framework of small molecules produced after the decomposition of Li2CO3. When sufficient lithium oxide acts as a nucleation skeleton at high temperature, the relevant glass crystal phase and grains are more stable and tend not to grow, so the thermal expansion coefficient is improved. On the contrary, when other systems of nucleation auxiliary components are used, such as phosphorus system, Zr system, etc., the stability of the nucleation skeleton is relatively poor. At the same time, the insulating properties of the sealing glass of each component of the embodiment, such as dielectric constant, insulation performance, and maximum breakdown voltage, are also slightly improved compared with the comparative example.

[0092] In addition, when the sealing glass component does not undergo an ultra-high temperature melting step during the preparation process (such as Comparative Example 4), the thermal expansion parameters increase significantly, which indicates that the nucleation-assisting effect of lithium oxide needs to be consolidated at a high temperature stage; and when the microcrystalline glass powder is cooled too quickly (such as Comparative Example 5), the microcrystalline glass grains are shaped too quickly and have no time to be homogenized, resulting in a relative degradation of the thermal expansion coefficient at high temperature.

[0093] In terms of the overall airtightness of the sealed device, the airtightness of the sealed device using the process of the present invention and the specific components of the sealing glass powder is higher than that of the control example. The airtightness after aging at high temperature is slightly lower than that at room temperature. Compared with the embodiment 1 and 2 of the present invention, the overall airtightness of the device is better, and it can also be maintained after long-term use at high temperature.

[0094] In this regard, the inventors tested the airtightness of the sealed samples of Example 1 and Comparative Example 1 after aging for 168 hours at 90°C in a high-temperature working environment, and longitudinally cut them apart from the alloy-sealed base (the connection between the alloy guide column and the bottom cover part), and then performed SEM scanning electron microscope tests after polishing. Figure 3 shown.

[0095] Figure 3 The SEM scanning electron microscope cross-sectional photograph on the left is a cross-sectional combination diagram shown in Example 1.

[0096] In the picture, since the alloy guide pillars are usually prepared by a high-temperature alloy drawing process, the grains become significantly larger, while the base part is usually obtained by a casting process, and the grains are relatively very fine. In the left figure, the alloy guide pillars and the bottom cover are firmly bonded to each other through sealing glass, without a gap in the middle, making it more airtight. In Comparative Example 1, due to the sudden decrease in the Li oxide content and the fact that other components do not play a better role in nucleation and crystal phase guidance, the glass / alloy interface at the interface is rough and partial gaps appear after high-temperature aging. Although the partial gaps are not enough to completely destroy the airtightness, this makes the airtight effect of the comparative example tend to deteriorate compared to the embodiment.

[0097] In addition, when the temperature curve for performing the fusion bonding process does not pass through the inert atmosphere insulation of the ultra-high temperature stage (such as Comparative Example 6), the airtightness test of the sealing device is deteriorated by one order of magnitude compared with the embodiment. This shows that the specific fusion glass component of the present application must pass through a high-temperature fusion sealing stage containing a specific curve in order to stabilize the skeleton formed by the excess Li oxide and allow the fusion microcrystalline glass grains to stably seal the iron-nickel metal components.

[0098] According to the implementation scheme and technical contents recorded in the specification of the present invention, the present invention can at least provide the following technical solutions: Although the present disclosure includes specific embodiments, it is obvious to those skilled in the art that various formal and detailed replacements or changes can be made to these embodiments without departing from the gist and scope of the invention of the present claims and their equivalent technical solutions. The embodiments described herein should be considered to be illustrative only and not for the purpose of limitation. The description of the features and aspects in each embodiment is considered to be applicable to similar features and aspects in other embodiments. Therefore, the scope of the present disclosure should not be limited by the specific description, but by the technical solutions of the claims, and all changes within the scope of the claims and their equivalents are interpreted as being included in the technical solutions of the present disclosure.

Claims

1. An alloy packaging process, characterized in that: The process seals an alloy product including a first alloy component and a second alloy component together by fusion sealing glass, wherein: The sealing glass is obtained by melting the following raw material powders through a high-temperature process, wherein the raw material powders include the following components in parts by weight: 50 to 80 parts by weight of SiO2, 20 to 40 parts by weight of ZnO, 5 to 20 parts by weight of Al2O3, 5 to 20 parts by weight of B2O3, 0.5 to 2 parts by weight of Na2CO3, 1 to 2 parts by weight of K2CO3, 2 to 10 parts by weight of TiO2, 25 to 60 parts by weight of Li2CO3; and Preferably, the mass ratio of SiO2 to Li2CO3 is 10:(4-9).

2. The alloy packaging process according to claim 1, characterized in that: The preparation of the sealing glass comprises the following steps: Mixing the components of the raw material powder, adding an organic solvent and grinding until the components of the raw material mixed powder are evenly mixed to obtain a raw material mixed powder material; The raw mixed powder material is heated to 1400°C to 1450°C and kept warm for 0.5 to 1 hour; then the temperature is raised to 1500 to 1550°C and kept warm for 1 to 2 hours; then the temperature is raised to 1590 to 1620°C and kept warm for 0.5 to 1 hour; then the glass blank is obtained by cooling at a cooling rate of 400 to 600°C / second, and then a sealing glass with an average particle size of 10μm to 20μm is obtained through a pulverizing process.

3. The alloy packaging process according to claim 1 or 2, characterized in that: The production of the sealing glass further comprises the following steps: Dispersing and bonding step: after weighing the raw material powder in proportion, prepare a dispersant in a mass percentage ratio of 1:(15-20) between the dispersant and the sealing glass, wherein the dispersant is selected from paraffin oil and / or refined paraffin; then, fully mix and cool the two at a temperature range of 90 to 100° C. to obtain glass small particles with an average particle size of about 50 mesh to 100 mesh; Wax removal step: remove wax from the small glass particles and then crush them to obtain the sealing glass.

4. The alloy packaging process according to any one of claims 1 to 3, characterized in that: The process of fusing and sealing an alloy product including a first alloy component and a second alloy component by sealing glass comprises the following steps: Alloy pretreatment step: taking the first alloy component and the second alloy component and pretreating them, preferably, the pretreatment includes one or more of the steps of cleaning, polishing and degreasing; Inert atmosphere sintering and melting bonding step: take the prepared sealing glass, the first alloy component and the second alloy component obtained after pretreatment, arrange the sealing glass at the place to be sealed between the first alloy component and the second alloy component, then place and fix them in a graphite mold, and perform sintering and melting bonding treatment under nitrogen protection.

5. The alloy packaging process according to any one of claims 1 to 4, characterized in that: The fusion bonding process includes the following specific processing temperatures and holding times: The temperature is raised uniformly to 500-520°C at a rate of 45-55°C / min; then, the temperature is raised uniformly to 860-865°C at a rate of 20-22°C / min; Subsequently, keep the temperature at 860-865 for 5-10 minutes; then, increase the temperature uniformly to 990-1000°C at a speed of 5-10°C / min; then, keep the temperature at 990-1000°C for 2-4 minutes; then, cool down to 450-460°C at a speed of 20-25°C / min; then, cool down to 250-260°C at a speed of 5-7°C / min; then, cool down to 20-30°C at a speed of 80-90°C / min.

6. The alloy packaging process according to any one of claims 1 to 5, characterized in that: The first alloy component and the second alloy component are selected from components made of an alloy containing iron and nickel; preferably, the first alloy component and the second alloy component are selected from components made of an alloy containing iron, cobalt and nickel; further preferably, the first alloy component and the second alloy component are selected from alloy components prepared from Kovar alloy.

7. The alloy packaging process according to any one of claims 1 to 6, characterized in that: The first alloy component is selected from the alloy guide column of the module assembly of the laser multistage tube, and the second alloy component is selected from the alloy cover bottom of the module assembly of the laser multistage tube; and Preferably, the process of sealing together by sealing glass fusion further comprises sealing together a third alloy component with the first alloy component and the second alloy component, wherein the third alloy component is selected from a metal shell of a module assembly of a laser multistage tube.

Citation Information

Patent Citations

  • Lead-free sealing glass powder having selective spectrum absorption characteristic, and manufacturing method thereof

    CN103910490A